An agricultural community’s perspectives on COVID-19 testing to support safe school reopening - Ramirez, Magaly; Bishop, Sonia; Ibarra, Genoveva; Shah, Parth; Duran, Miriana C.; Chae, Hwa Young; Hassell, Laurie; Garza, Lorenzo; Linde, Sandra; Garrison, Michelle M.; Drain, Paul K.; Ko, Linda K. (Frontiers in Public Health, 2023)
Introduction School-based COVID-19 testing may be an effective strategy for reducing transmission in schools and keeping schools open. The study objective was to examine community perspectives on school-based COVID-19 testing as a mitigation strategy to support safe school reopening. Methods We conducted a qualitative study in Yakima County, an agricultural region of Washington state, where over half of residents are Hispanic/Latino. From June to July 2021, we interviewed 18 students (13 years old, on average) and 19 school employees, and conducted four focus groups (2 in Spanish, 2 in English) with 26 parents. We audio-recorded the semi-structured interviews and focus group discussions which were then transcribed. We used an inductive, constant comparison approach to code the transcripts and conducted a thematic analysis to generate themes. Results We identified four main themes. Students, parents, and school employees desired a return to in-person learning (Theme 1). Schools implemented numerous COVID-19 mitigation strategies (e.g., masking) to facilitate a safe return to school but felt that adding testing would not be feasible due to a lack of resources and overworked staff (Theme 2). Parents and school employees’ familiarity with COVID-19 testing procedures influenced their support for testing (Theme 3). Parents and school employees felt there were inadequate resources for individuals who test positive for COVID-19 (Theme 4). Discussion Schools require adequate resources and medical personnel to implement COVID-19 testing. Individuals also need resources after testing positive, including physical space to isolate, financial resources for those without paid time off, and delivery of food and other necessities to households in rural communities.